Global water resources affected by human interventions and climate change - Haddeland, Ingjerd; Heinke, Jens; Biemans, Hester; Eisner, Stephanie; Flörke, Martina; Hanasaki, Naota; Konzmann, Markus; Ludwig, Fulco; Masaki, Yoshimitsu; Schewe, Jacob; Stacke, Tobias; Tessler, Zachary D.; et al. (National Academy of Sciences, 2014)
Humans alter the water cycle by constructing dams and through water withdrawals. Climate change is expected to additionally affect water supply and demand. Here, model analyses of climate change and direct human impacts on the terrestrial water cycle are presented. The results indicate that the impact of man-made reservoirs and water withdrawals on the long-term global terrestrial water balance is small. However, in some river basins, impacts of human interventions are significant. In parts of Asia and the United States, the effects of human interventions exceed the impacts expected for moderate levels of global warming. This study also identifies areas where irrigation water is currently scarce, and where increases in irrigation water scarcity are projected.